1991
DOI: 10.1007/bf03008186
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide responses during anaesthesia in patients with refractory cardiomyopathies

Abstract: In patients with congestive heart failure, the release of atrial natriuretic peptide (ANP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(3 reference statements)
2
1
0
Order By: Relevance
“…Similar unfavourable haemodynamic effects of ketamine have been reported in previous studies during induction of anaesthesia in patients with cardiomyopathy undergoing heart transplantation 8,9 . However, in these studies any adverse longterm haemodynamic effects of ketamine were without consequence, since the diseased heart was removed soon after drug application.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar unfavourable haemodynamic effects of ketamine have been reported in previous studies during induction of anaesthesia in patients with cardiomyopathy undergoing heart transplantation 8,9 . However, in these studies any adverse longterm haemodynamic effects of ketamine were without consequence, since the diseased heart was removed soon after drug application.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, both studies revealed also a significant adverse effect related to an undesirable ketamineinduced increase in pulmonary artery pressure. This potential negative effect of ketamine infusion has also been demonstrated in other studies with cardiac patients [8][9][10] . As pulmonary vascular resistance is often already elevated in septic patients and patients with pulmonary or cardiac disease, further increases of right ventricular afterload by ketamine might be of clinical relevance.…”
Section: Discussionsupporting
confidence: 67%
“…However, a lack of relation between sedation and sodium excretion has been reported in the literature 44 and most of our patients were constantly sedated during periods 1 and 2 when the most consistent changes were observed.…”
Section: Discussionmentioning
confidence: 46%